Identifying strategies and related principles supporting a co-design approach in an assistive device service delivery and research platform - Jeyakumaran, Thuvaraha; Eggiman-Ketter, Jordan; Spadzinski, Abby; Wolfe, Dalton L. (Frontiers in Rehabilitation Sciences, 2024)
IntroductionPossibilities Project Plus (PPPlus) is a free assistive device (AD) marketplace and research platform for persons with disabilities. The overall aim of PPPlus is to increase access to ADs through an integration of service, research and education. To maximize positive outcomes and reflect community needs a co-design approach informed by guiding principles of Integrated Knowledge Translation (IKT) was adopted, with examination of methods related to Experience Based Co-design. The integrated nature of PPPlus benefits from the use of specific engagement strategies that align with IKT principles to meet project objectives. The extent to which partnership and engagement strategies are specified in the rehabilitation research literature vary greatly and studies that provide information on specific strategies used to operationalize principles are limited. The objective of this manuscript is to provide a description of the co-design approach and the specific strategies that strive to achieve meaningful user engagement. By reflecting on these processes we also report on limitations and strategies for improvement.MethodsThe co-design approach is highlighted through specific project activities including a representative governance structure, ongoing environmental scan and iterative Health Equity Impact Assessments (HEIA). The inherent engagement strategies that align with IKT and co-design principles are described.DiscussionThe most impactful engagement strategies included early engagement of partners throughout all phases, ensuring project relevance across partners through alignment of objectives with complementary aims, using HEIAs to promote equitable outcomes from diverse stakeholders, the representative governance structure beyond individuals with disabilities and caregivers, and the use of experiences and stories to inform development.Next stepsThis examination of specific strategies related to co-design focused on partnership engagement and informed targets for enhancement of the PPPlus initiative. These include being more intentional in developing a more rigorous process for evaluation that includes an assessment of strategies and their impact—especially as related to partner engagement. In addition, ongoing and enhanced efforts will focus on developing knowledge products that bring to life the most salient experience-based user stories emerging from the environmental scan with these being used to drive distinct co-creation events as well as serve other knowledge mobilization purposes (i.e., supporting policy change).